Pengaruh Peran Kepala Sekolah, Iklim Sekolah, Dukungan Pembelajaran, dan Program Kewirausahaan Terhadap Minat Kewirausahaan Siswa - Ismawati Ismawati; Syarifuddin Syarifuddin; Rahmawati Rahmawati (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study examined the influence of the principal's role, school climate, learning support, and entrepreneurship programs on the entrepreneurial interest of grade XII students at SMAN 2 Kepulauan Selayar. A quantitative ex post facto design was used with 141 students selected through proportional random sampling. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression with t-test, F-test, and coefficient of determination. The results showed that all predictors had positive and significant effects on entrepreneurial interest. The principal's role had a significant effect (t = 2.573; p = 0.011), school climate had a significant effect (t = 2.899; p = 0.004), learning support had a significant effect (t = 2.859; p = 0.005), and entrepreneurship programs had a significant effect (t = 2.574; p = 0.011). The simultaneous test was significant (F = 17.990; p < 0.001). The model explained 34.6% of the variance in entrepreneurial interest. These findings indicate that entrepreneurial interest is strengthened by integrated managerial, social, pedagogical, and programmatic support within the school ecosystem.